Market reactions towards the appointment of women to the boards of Malaysian firms - Ku Ismail, Ku Nor Izah; Abdul Manaf, Kamarul Bahrain (Elsevier B.V., 2016)
This study examines market reactions towards the appointment of women to corporate boards and observes if women’s attributes as well as the role that they play in discharging their monitoring responsibilities would affect the value of firms. We observe 127 Malaysian firms that appoint women directors over the period 1999–2011.We use the market model to assess abnormal returns surrounding the appointment of women directors from day −10 to day 10. Using conventional t-test, share time series test and rank test, we find that investors welcome the appointment of women directors.A positive average abnormal return (AAR) is observed on day −1 using all the three tests. Cumulative average abnormal returns (CAAR) are positive over the period day 1 to day 10.We also find that investors are more likely to favour women who are prominent, younger, have no international exposure and no family relationship with any other directors.Our findings support the initiative taken by the Malaysian Government to promote greater women participation on corporate boards. Policy makers may benefit from this study because it provides them an input at enhancing the policy related to women on boards.